Development and Validation of the Chinese Version of the Highly Sensitive Child Scale: Understanding environmental sensitivity and depressive symptoms in adolescents - Dong, Qian; Zhou, Lina; Wang, Wei; Wei, Xin; Pluess, Michael; Ma, Xiancang (Frontiers in Psychiatry, 2022)
Background: Environmental sensitivity (ES) is considered a significant personality factor in the development and maintenance of depressive symptoms in adolescents. However, a clear instrument that can capture ES in Chinese adolescents is lacking. The current study aimed to investigate the psychometric properties of a Chinese version of the Highly Sensitive Child (HSC) scale for assessing adolescent ES, and explore the potential moderation effect of ES on relationships between maternal behaviors and adolescent depressive symptoms. Method: In total, 2,166 students from 4 middle and high schools and 105 depressed adolescents completed measurements of environmental sensitivity, maternal behaviors, depressive emotions, sleep duration, and academic performance. Results: First, exploratory factor and confirmatory factor analyses indicated that the HSC scale had a good model fit with the bifactor construct, total scale reliability was adequate-good, and measurement invariances across genders and different samples were supported. Furthermore, the results confirmed that the relationship between maternal behaviors and adolescent depressive symptoms had small effects. Compared to low environmentally sensitive adolescents, high environmentally sensitive adolescents exhibited less depressive emotions and better academic performance in the context of high-quality maternal behaviors. Low-quality maternal behaviors significantly predicted increased depressive emotions and worse academic performance in adolescents when environmental sensitivity was high. Moreover, on the contrary, maternal behaviors did not influence depressive emotions and academic performance in adolescents who were less sensitive to their environment. The relationship between maternal behaviors and adolescent depressive symptoms is influenced by different levels of environmental sensitivity. Conclusions: Our findings support the HSC scale as a comprehensive and psychometrically robust tool to measure ES in Chinese adolescents. In addition, the present study clarifies the moderating role of environmental sensitivity underlying the relationship between maternal behaviors and adolescent depressive symptoms. It is important to consider the role of ES in prevention and intervention strategies targeting adolescent depressive symptoms.